Laboratory Identification of Lupus Anticoagulants - Kershaw, Geoffrey; Suresh, Sasikala; Orellana, Daniel; Nguy, Yun-Mi (Seminars in Thrombosis and Hemostasis, 2012)
The main laboratory characteristic of lupus anticoagulants (LA) is their ability to prolong phospholipid-dependent clotting time in vitro. The laboratory demonstration of LA requires a systematic approach combined with an awareness of the many variables that can affect test results. The ideal testing procedures are those sensitive enough to detect weak LA and specific enough so as not to produce incorrect conclusions. International guidelines have been published to assist laboratories in applying correct testing processes. The most recently published guidelines from the International Society on Thrombosis and Haemostasis update the criteria for detecting the presence of LA that were presented in the 1995 guidelines. Some of the specific recommendations relate to the key areas of setting cut-off levels for screening, mixing, and confirmatory procedures. The more challenging aspects of testing for LA include maintaining sensitivity and specificity of the assays, especially in the presence of anticoagulant therapy.
Keywords: lupus anticoagulant; diluted Russell viper venom time; activated partial thromboplastin time; mixing test